Study of Some Physical Properties of the Superconducting Compound PbBa2Ca2Cu3O8+δ - Ali, Fouad Waheed; Jasim , Kareem Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
To analyze the structural properties of the PbBa2Ca2Cu3O8+δ sample, an X-ray diffraction analyzer was used. The results showed that the compound has a tetragonal crystal structure. The crystal lattice constants (a, b, and c) were calculated based on the crystal lattice properties. The crystal size was calculated by four different methods (Scherrer, Williamson-Hall, Halder-Wagner, and size-strain plot), and the best result of  C. S = 88.49 nm was for the Halder-Wagner method among other methods. The titration method was used for the samples to find out the percentages of oxygen content (δ). It was found that the oxygen content was (δ = 0.279). Four probes method was used to determine the transition temperature, and it was found that the transition is (T(onset) =138K ) The electrical resistance starts with a strong gradient and becomes zero at the critical temperature (T(offset)=110K) using Lee's disk method. The results showed that the thermal conductivity of the sample decreases with increasing temperature, as the sample is characterized by a phase (PbBa2Ca2Cu3O8+δ) with a thermal curve. The thermal conductivity starts at (0.12197) for (313K), and the curve decreases at (0.104288) for (553K). The  LCR meter device in the range of (50 Hz) to (1 MHz) at room temperature to calculate the dielectric properties of the sample, which include the real dielectric constant (3.58758) and imaginary dielectric constant (10.1710) at frequency (50 Hz),  the value of the dielectric constant (real and imaginary) (0.08099, 0.00758) at frequency (1 MHz), and an increase in alternating conductivity values (4.8667*10-7) when the frequency is increased to (1 MHz). One of the most important applications of magnetic resonance imaging is high-speed trains and some modern communication devices